Polyphenol deposition in leaf hairs of Olea europaea (Oleaceae) and Quercus ilex (Fagaceae) (AMERICAN JOURNAL OF BOTANY, 1998)
The subcellular localization (cytoplasm, vacuoles, cell walls) of polyphenol compounds during the development of the multicellular nonglandular leaf hairs of Olea europaea (scales) and Quercus ilex (stellates), was investigated. Hairs of all developmental stages were treated with specific inducers of polyphenol fluorescence, and the bright yellow-green fluorescence of individual hairs was monitored with epifluorescence microscopy. During the early ontogenetic stages, bright fluorescence was emitted from the cytoplasm of the cells composing tie multicellular shield of the scales of O. europaea. Transmission electron micrographs of the same stages showed that these cells possessed poor vacuolation and thin cell walls. The nucleus of these cells may be protected against ultraviolet-B radiation damage. The progressive vacuolation that occurred during maturation was followed by a shifting of the bright green-yellow fluorescence from the perinuclear region and the cytoplasm to the cell walls. The same trends were observed during the development of the nonglandular stellate hairs of Quercus ilex, in which maturation was also accompanied by a considerable secondary thickening of the cell walls. Despite the differences in morphology, high concentrations of polyphenol compounds are initially located mainly in the cytoplasm of the developing nonglandular hairs, and their deposition on the cell walls rakes place during the secondary cell wall thickening. These structural changes during the development of the leaf hairs make them a very effective barrier against abiotic (UV-B radiation) and probably biotic (pathogenic) stresses.

Trichome density and its UV-B protective potential are affected by shading and leaf position on the canopy (Environmental and Experimental Botany, 1997)
In Olea europaea trichome density and UV-B absorbing compounds of leaf hairs and the lamina proper of leaves located in south-facing, north-facing and the internal of the canopy were positively correlated to the UV-B midday instant irradiance measured in September at these three different positions of the canopy. The correlation between these three parameters and the receiving photosynthetically active radiation (PAR), however, was weaker. In Quercus ilex, trichome density and its UV-B absorbing capacity were considerably higher in the exposed, south-facing leaves, compared to the deeply shaded ones; the UV-B absorbing capacity of the de-haired lamina, however, was the same. In the broad- leaved, alpine rosette of Verbascum speciosum, one could distinguish two areas on the leaves, one exposed and one shaded by the superimposed lamina. Although trichome density and the UV-B absorbing compounds of the de-haired leaf were the same in the two areas, the UV-B absorbing capacity of hairs was considerably increased in the exposed region. In V. speciosum, exposure induced also qualitative changes in the UV-B absorbance profile, apparently due to the formation of new flavonoid compounds absorbing maximally at 345-350 nm. In all other cases, the differences were mainly quantitative. The results support the postulate of a function of leaf hairs as a UV-B radiation screen and suggest that trichome density and/or its UV-B absorbing capacity may depend on irradiance during leaf development.